Navigated Antral Bone Expansion (NABE): a prospective study on 35 patients with 4 months of follow-up post implant loading - Luigi V. Stefanelli; Nicola Pranno; Francesca De Angelis; Silvia La Rosa; Antonella Polimeni; Stefano Di Carlo (BMC, 2020)
Abstract Background The insertion of dental implants in the atrophic posterior maxilla can be a challenge. One option is to modify the residual native bone in preparation for proper, prosthetically-driven implant placement. The procedure presented in this study is called Navigated Antral Bone Expansion (N.A.B.E). This procedure employs the use of a navigation system to plan and guide the initial pilot drilling, bone expansion, final site preparation, and implant insertion. The aim of this study was to compare the distance between the alveolar ridge and the sinus floor measured before and after the surgery performed using the N.A.B.E. technique. Methods Thirty-seven partially edentulous patients who were candidates for implant supported restoration in the posterior maxilla, with a bone height ranging from 4 to 7 mm were enrolled. The N.A.B.E procedure was used to increase the bone height. Paired-samples t-test evaluated the distance between the alveolar ridge and the sinus floor measured before and after surgery. The occurrence of post-surgical complications, and the angular deviation between the planned osteotomy and the actual placed implant trajectories were evaluated. Results Out of the 37 consecutive patients enrolled in the study, 35 were considered in the data analyses. Patients' bone height after surgery compared to the bone height before surgery showed a statistically significant increase (p < .0005) of 3.96 mm (95% CI, 3.62 mm to 4.30 mm). No post-operative complications were observed in the 35 patients. The mean angular deviation between the planned osteotomy trajectory and the placed implant trajectory ranged between 12.700 to 34.900 (mean 25.170 ± 5.100). Conclusions This study provides evidence that N.A.B.E. technique is able to provide a significant bone increase, and could be considered an alternative method to the management of the atrophic posterior maxilla with a minimally invasive approach.